Morphological characteristics of Chinese jujube leaves in connection with varietal identification - T. V. Shishova (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Establishment and replenishment of plant collections are associated with the exchange of vegetative germplasm. When establishing new or reconstructing old plantings, there is always a possibility of misidentification. A detailed morphological description of the jujube leaf was carried out to accelerate and increase the efficiency of plant identity testing.Materials and methods. The leaves of 26 Chinese jujube (Ziziphus jujuba Mill.) cultivars of foreign and domestic origin served as the material for the study. Quantitative parameters of the leaf (length, width, shape index, and petiole length) and their coefficients of variation were calculated. Qualitative indicators (leaf blade, apex, base, and edge shapes) are described. The description of the leaf’s main characteristics was in line with the procedure approved for testing distinctiveness, uniformity and stability in Ziziphus sativa Gaertn.Results. The average leaf length varied among cultivars from 4.35 to 8.11 cm, and the width from 2.61 to 4.69 cm (CV = 15.90 and 15.04%, respectively). The petiole length variation was stronger: 2.72 to 10.0 mm (CV = 28.10%). Ovate leaves had a shape index from 1.52 to 1.99, while the length of elliptic leaves was more than twice greater than their width (shape index: 2.01 to 2.36). Characteristic leaf features were identified for four cultivars; they will accelerate their testing. Qualitative and quantitative leaf characteristics were described for 4 cultivars recommended for cultivation in Russia.Conclusion. The leaf’s characteristic features or their combinations were identified for individual cultivars and their groups of origin. The greatest diversity and variation in characteristics were observed in the cultivars from China and those developed at the Nikita Botanical Gardens. The results were used for varietal identification of Chinese jujube plants in the newly established collection and nurseries.